VISUALIZING SPEECH ACOUSTIC FEATURES BY USING COMPUTERIZED PROGRAMS IN THE CONTEXT OF PROFOUND HEARING IMPAIRMENTS - CAROLINA HATEGAN (Studia Universitatis Babes-Bolyai, 2010)
ABSTRACT. Through this article it is underlined the way two computerized programs can be complementary used (Cool Edit Pro and Praat) in order to visualize speech acoustic features in the context of profound hearing impairment. The linguistic material that was used was both isolated sounds and co-articulated sounds at word level. The participants in the research are profoundly hearing impaired persons, both using verbal language, one person wearing digital hearing prosthesis and one without benefits from technical aid.